"Наталка Полтавка" Івана Котляревського в українському мовно-культурному просторі - Мех, Н. (Культура слова, 2019)
У статті зроблено спробу поглянути на п’єсу «Наталка
Полтавка» в широкому мовно-культурному вимірі. Розглянуто твір
як першу спробу новою українською мовою говорити про українство
правдиво, яскраво, дотепно. Особливу увагу приділено пісням драми,
які живуть окремим мистецьким життям. Розглянуто значення
твору І. Котляревського для музичної царини, зокрема – оперу Миколи
Лисенка за однойменною п’єсою «Наталка Полтавка» як знакову
подію в українському культурному просторі.
Шана до моральної чистоти, духовної сили, народної мудрості
та мови, любов та повага до простих людей – все це ми бачимо в
талановитій п’єсі Івана Котляревського. The article attempts to look at Natalka Poltavka’s play in a broad
linguistic and cultural dimension. The work is considered as the first
attempt in a new Ukrainian language to speak about Ukrainian truthfully,
brightly and wisely. Particular attention is paid to songs of drama that live
separate artistic lives. The importance of the work of I. Kotlyarevsky for
the musical realm, in particular, the opera of Mykola Lysenko based on
the play “Natalka Poltavka” as a landmark event in the Ukrainian cultural
space, is considered.
Natalka Poltavka Opera is a real pearl of Ukrainian music. It clearly
reveals national life, typical characters and traditions thanks to the folklorebased
music. Key opera songs have long gone beyond it and are perceived
in various parts of the world as symbols of Ukrainian culture.
Natalka Poltavka is the first work of the new Ukrainian dramaturgy,
combining signs of sentimentalism and educational realism. At the time
when the play was written, sentimentalism began to develop rapidly in
European literature, which was characterized by the desire to recreate
the world of the feelings of the common man and to evoke sympathy for
the heroes of the work. We notice these tendencies in drama, watching
I. Kotlyarevsky appeal to human feelings, focusing on their strength,
sincerity and depth.
Respect for moral purity, spiritual strength, popular wisdom and
language, love and respect for ordinary people are all we see in Ivan
Kotlyarevsky’s talented play.